Religious and ethical perspectives on global migration - Collier, Elizabeth W.; Strain, Charles R. (Lexington Books, 2014)
"Religious and Ethical Perspectives on Global Migration examines the complicated social ethics of migration in today's world. Editors Elizabeth W. Collier and Charles R. Strain bring the perspectives of an international group of scholars toward a theory of justice and ethical understanding for the nearly two hundred million migrants who have left their homes seeking asylum from political persecution, greater freedom and safety, economic opportunity, or reunion with family members. Migrants move out of fear, desperation, hope, love for their families, or a myriad of other complex motivations. Faced with both the needs and flows of people and the walls that impede them, what actions ought we, both individually and collectively, take? What is the moral responsibility of those of us, in particular, who reside comfortably in our native lands? There is no univocal response to these questions. Instead multiple perspectives on migration must be examined. This book begins by looking at different geographic regions around the world and highlighting particular issues within each. Finding that religious traditions represent the strongest countervailing sources of values to the homogenizing tendencies of economic globalization, the study then offers a plurality of religious perspectives. The final chapters examine the salient issues and the proposed solutions that have emerged specifically within the U.S. context. These studies range from militarization of the U.S. border with Mexico to the impact of migrants on native-born low-skilled workers. Encompassing a wide range of cultural and scholarly voices, Religious and Ethical Perspectives on Global Migration provides insight for ethics, moral philosophy, social and political philosophy, religious studies, social justice, globalization, and identity formation"--Unedited summary from book cover.